Physicochemical Properties of Ti3+ Self-Doped TiO2 Loaded on Recycled Fly-Ash Based Zeolites for Degradation of Methyl Orange - Iván Supelano García; Carlos Andrés Palacio Gómez; Marc H. Weber; Indry Milena Saavedra Gaona; Claudia Patricia Castañeda Martínez; José Jobanny Martínez Zambrano; Hugo Alfonso Rojas Sarmiento; Julian Andrés Munevar Cagigas; Marcos A. Avila; Carlos Rettori; Carlos Arturo Parra Vargas; Julieth Alexandra Mejía Gómez (Condensed Matter, 2022)
The extensive production of coal fly ash by coal combustion is an issue of concern due to its environmental impact. TiO2-zeolite composites were synthesized, at low cost, using recycled coal fly ash from a local thermoelectric power plant to produce the zeolite using the hydrothermal method. TiO2 was loaded by means of the impregnation method using ethanol and titanium isopropoxide between 8.7 and 49.45 wt% TiO2. The samples were characterized by X-ray diffraction, Raman, electron spin resonance, high-resolution transmission electron microscopy, N2 adsorption-desorption, doppler broadening of annihilation radiation, and diffuse reflectance techniques, and the photocatalytic activity of the composites was evaluated according to the degradation of methyl orange under UV light. The results show that TiO2 crystallizes in the anatase phase with a Ti3+ oxidation state, without post-treatment. TiO2 particles were located within the pores of the substrate and on its surface, increasing the surface area of the composites in comparison with that of the substrates. Samples with TiO2 at 8.7 and 25 wt% immobilized on hydroxysodalite show the highest degradation of methyl orange among all studied materials, including the commercial TiO2 Degussa P25 under UV light.